2019
DOI: 10.1021/acsomega.9b02861
|View full text |Cite
|
Sign up to set email alerts
|

A “One-Pot” Route for the Synthesis of Snowflake-like Dendritic CoNi Alloy-Reduced Graphene Oxide-Based Multifunctional Nanocomposites: An Efficient Magnetically Separable Versatile Catalyst and Electrode Material for High-Performance Supercapacitors

Abstract: In this paper, a simple “one pot” methodology to synthesize snowflake-like dendritic CoNi alloy-reduced graphene oxide (RGO) nanocomposites has been reported. First-principles quantum mechanical calculations based on density functional theory (DFT) have been conducted to understand the electronic structures and properties of the interface between Co, Ni, and graphene. Detailed investigations have been conducted to evaluate the performance of CoNi alloy and CoNi-RGO nanocomposites for two different types of app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
43
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(46 citation statements)
references
References 91 publications
(210 reference statements)
3
43
0
Order By: Relevance
“…14) also supported this fact by demonstrating the higher conductivity of Co-Ni-graphene nanocomposite. 129 Similar observations were attained when we have carried out DFT calculations for the Ag-Ni-rGO catalysts, to explain why The enhancement of catalytic efficiency of core-shell Ag@Pt nanoparticles due to their immobilization on the sepiolite nanobers towards the reduction of 4-NP has been reported by Ying Ma et al 138 DFT calculations were performed to determine the plausible reaction mechanism and to realize the electronic structure and interaction of Ag cores and Pt shells in the Ag@Pt nanoparticles. The higher TDOS of Ag@Pt than that of Ag suggested the higher catalytic activity of Ag@Pt.…”
Section: Metal Nanoparticle Catalyzed Reduction Of 4-nitrophenol To 4-aminophenolsupporting
confidence: 77%
See 3 more Smart Citations
“…14) also supported this fact by demonstrating the higher conductivity of Co-Ni-graphene nanocomposite. 129 Similar observations were attained when we have carried out DFT calculations for the Ag-Ni-rGO catalysts, to explain why The enhancement of catalytic efficiency of core-shell Ag@Pt nanoparticles due to their immobilization on the sepiolite nanobers towards the reduction of 4-NP has been reported by Ying Ma et al 138 DFT calculations were performed to determine the plausible reaction mechanism and to realize the electronic structure and interaction of Ag cores and Pt shells in the Ag@Pt nanoparticles. The higher TDOS of Ag@Pt than that of Ag suggested the higher catalytic activity of Ag@Pt.…”
Section: Metal Nanoparticle Catalyzed Reduction Of 4-nitrophenol To 4-aminophenolsupporting
confidence: 77%
“…136 We have also developed CoNi-rGO and AgNi-rGO nanocatalysts for the reduction of 4-NP. 129,131 Our experimental results indicated that the catalytic activity of pure metal nanoparticles (i.e., Co, Ni, Ag) was less than that of bimetallic alloy catalysts (e.g., Co-Ni, Ag-Ni) and when the bimetallic alloy nanoparticles were anchored on the RGO support, the catalytic efficiency was further enhanced. We have performed DFT calculations to know the interfacial interactions (i) between metal nanoparticles in the bimetallic alloy system (e.g., Co-Ni, Ag-Ni) and (ii) between alloy nanoparticles and the graphene in the nanocatalysts.…”
Section: Metal Nanoparticle Catalyzed Reduction Of 4-nitrophenol To 4-aminophenolmentioning
confidence: 81%
See 2 more Smart Citations
“…The synthesis of the snowake-like dendritic (CoNi D ) 60 RGO 40 nanocomposite and its catalytic and supercapacitor applications were presented in this study. 276 Multifunctional and stimuli-responsive MNP-and derivative nanocomposite-based systems have emerged from nanobiotechnology with signicant impacts on drug delivery, cancer diagnosis and treatment. These systems overcome the limitations of conventional therapeutic methods for cancer in recent decades.…”
Section: Multifunctional Micro and Nanoscale Magnetic Catalytic Systemsmentioning
confidence: 99%